2007
DOI: 10.1097/01.mlg.0000249935.81808.df
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Continuity of Longitudinal Pharyngeal and Esophageal Muscles

Abstract: This study demonstrates that the longitudinal pharyngeal and esophageal muscle fibers are continuous with each other and are integrated with fibrous and cartilaginous structures. Such anatomic integrity at the pharyngoesophageal junction is important for the function of the upper esophageal sphincter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Also, a recent study on 30 cadavers showed that upper longitudinal esophageal muscle fibers are anatomically continuous with the pharyngeal muscles, highlighting the importance of the contribution of the upper esophagus to UES function. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Also, a recent study on 30 cadavers showed that upper longitudinal esophageal muscle fibers are anatomically continuous with the pharyngeal muscles, highlighting the importance of the contribution of the upper esophagus to UES function. 15 …”
Section: Discussionmentioning
confidence: 99%
“…In general, the palatopharyngeus is inserted into the piriform fossa and the posterior border of the thyroid cartilage [3,[15][16][17][18][19][20]. Okuda et al [17] have reported that the palatopharyngeus sometimes interlaces with the inferior constrictor.…”
Section: Discussionmentioning
confidence: 99%
“…The palatopharyngeus is one of the essential muscles required in proper swallowing, because it contributes to its various events, such as the movement of the soft palate, the shortening of the pharynx, and the elevation of the hyolaryngeal complex [3,7,8,[12][13][14]. The evidence of these contributions has been anatomically explained based on its attachments to the soft palate, the pharyngeal raphe, the epiglottis, and the thyroid cartilage [15][16][17][18][19][20]. Fukino et al [20] reported that the palatopharyngeus spreads radially and extends inferiorly.…”
Section: Introductionmentioning
confidence: 99%
“…We assume that a larger defect of the outer fascia had either occurred intraoperatively or was preexisting. The latter might be explained by the presence of preexisting thinner regions or even circumscribed absence of fibrous reticulation as the longitudinal esophageal and pharyngeal muscles merge to a membrane-like fascia that anchors the pharyngoesophageal wall to the surroundings [3] .…”
Section: Discussionmentioning
confidence: 99%